Methanesulfonic Acid (MSA) in Hydrometallurgy - Binnemans, Koen; Jones, Peter Tom (Journal of sustainable metallurgy, 2023)
This paper reviews the properties of methanesulfonic acid (MSA) and its potential for use in hydrometallurgy. Although MSA is much less known than sulfuric, hydrochloric or nitric acid, it has several appealing properties that makes it very attractive for the development of new circular flowsheets in hydrometallurgy. Unlike other organic acids such as acetic acid, MSA is a very strong acid ( pK a =  − 1.9). In addition, it is very stable against chemical oxidation and reduction, and has no tendency to hydrolyze in water. In terms of its environmental impact, MSA has low toxicity and is biodegradable. In nature, it is part of the geochemical sulfur cycle. A useful property is the high solubility of its salts in water: methanesulfonate salts have a much higher solubility in water than sulfate salts. Additionally, MSA and its salts are compatible with the electrowinning of metals because the anode reaction involves the formation of oxygen gas (unlike chlorine gas formation in chloride electrolytes) and no cathodic reduction of the anion occurs (unlike nitrate reduction in nitrate electrolytes). MSA is particularly interesting for lead hydrometallurgy, where it offers more environment-friendly alternatives to HBF 4 and H 2 SiF 6 . However, MSA can also be adopted in all hydrometallurgical processes that require strong Brønsted acids. It can be used in the metallurgy of copper, zinc, cobalt, nickel, and rare earths, as well as in the recycling of metals from end-of-life products. Although MSA itself is a non-oxidizing acid, in combination with hydrogen peroxide it yields strongly oxidizing lixiviants that can leach copper from chalcopyrite or dissolve metallic silver. The global production of MSA is expected to increase rapidly in the near future thanks to both the industrialization of a new sustainable synthesis process and its many applications (cleaning fluids, electrolytes for electroplating, redox-flow batteries, catalysts in organic synthesis, and as a solvent for high-molecular-weight polymers). As a result, MSA will become more widely available and a lower price will make it an increasingly attractive option. Graphical Abstract